The Baptist Western Association 1653–1658 - Nuttall, Geoffrey F. (The journal of ecclesiastical history, 1960)
The identification of a tract without title-page or caption title in the Library of the Society of Friends in London, together with the location in the Library of the Baptist College, Bristol, of another tract of which no copy was known to exist, makes it possible for the first time to summarise fully the beginnings of the Baptist Western Association. The Association's activity, apart from days spent in waiting upon God in fasting and prayer, was twofold: the resolution of queries submitted by the churches represented; and the issuing of circular letters of exhortation to the churches. Circular letters issued from nine of the Association's first ten meetings are printed in the first of the tracts mentioned, queries submitted and resolved at nine of the meetings in the second. From other sources we know that in 1655 the Association ordained as its superintendent Thomas Collier, the editor of both tracts; and that in 1656 it issued a Confession of the Faith. An assembly of ‘messengers’ or representatives of churches in the South-Western counties of England, meeting normally once in the spring and once in the autumn, the Western Association was a pioneer among those regional associations of churches which have ‘always been a feature of Baptist life’. Correct information concerning its meetings and leaders, and the churches represented, is thus desirable. The fifty-seven queries, moreover, with the answers they received, throw light upon issues then the concern of many beyond Baptist circles.